Galaxy clusters: Radio relics from fossil electrons - Johnston-Hollitt, Melanie (NATURE PUBLISHING GROUP, 2017)
The detection of a tailed radio galaxy in a galaxy cluster conjoined to a region of diffuse radio emission confirms that radio galaxies provide the energetic electrons needed to explain the origin of this enigmatic emission.